INTELLECTUAL PROPERTY LAW - Azimova Fatima Saidkarim kizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article delves into the multifaceted realm of intellectual property law, examining its significance in safeguarding creative and innovative endeavors. Through a comprehensive review of existing literature, this paper explores the evolution of intellectual property law, analyzes key concepts and principles, and offers insights into the methods employed for protecting intellectual assets. The article concludes with a discussion of the implications of intellectual property law on innovation and creativity, presenting suggestions for future developments in this dynamic field.